The Cambridge companion to modernist women writers - Linett, Maren Tova (Cambridge companions to topics., 2010)
"Women played a central role in literary modernism, theorizing, debating, writing, and publishing the critical and imaginative work that resulted in a new literary culture during the early twentieth century. This volume provides a thorough overview of the main genres, the important issues, and the key figures in women's writing during the years 1890-1945. The essays treat the work of Woolf, Stein, Cather, H. D. Barnes, Hurston, and many others in detail; they also explore women's salons, little magazines, activism, photography, film criticism, and dance. Written especially for this Companion, these lively essays introduce students and scholars to the vibrant field of women's modernism"--